PENGARUH PERTUMBUHAN EKONOMI, UKURAN PEMERINTAH DAERAH, DAN PENDAPATAN ASLI DAERAH TERHADAP KELEMAHAN SISTEM PENGENDALIAN INTERN (Studi Pada Pemerintah Kabupaten/Kota di Indonesia) - Abdul Majid (Master of Management, Mataram University, 2017)
The purposed of the study was to test the influence of economic growth, the local size government and local revenue to internal control system weakness of local government.The thesis is associative research. The population in this thesis are all regency / city in Indonesia and the scope of the discussion was about the influence of economic growth, the local size goverment, and local revenues, in cases of weakness of internal control systems in 2013. The samples were determined by using purposive sampling by total amount of the datas were 229, the total samples obtained 146 districts and cities in Indonesia by Slovin sampling formula. Data obtained through the Result of BPK’s Summary In 2014, The APBD’s Realization Statement, Balance Sheet Regions obtained from the website of the Directorate General of Fiscal Balance, the Finance Ministry of Republic Indonesia and APBD’s Realization Statement which was obtained from Respective of Regional Revenue each district/city government and the regional balance provided report of the asset which was a measure of local governments and economic growth through the BPS’s data. The results of this study showed the economic growth was positive influance in internal control system weakness, local size governments was negative influance in internal control syistem weakness, and the local revenues was positive influance in internal control system weakness but its unsignificant.Keywords : internal control system weakness, economic growth, local size government, and local revenues.